2019
DOI: 10.4103/jmas.jmas_229_17
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of minimally invasive surgery for patients presenting with suspected gallbladder cancer: Report of 8 cases

Abstract: The results of the present study confirm the short-term safety and feasibility of MIS for patients with GBCa, as all eight patients underwent successful MIS with no major morbidity or mortality. Further studies with larger patient cohorts with long-term follow-up are needed to determine the oncologic outcomes and the definitive role of MIS in treating GBCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 1 - 3 Laparoscopic surgery confers many benefits such as smaller surgical scars, reduced blood loss, and faster recovery times. 4 - 6 Nonetheless, its widespread adoption remains restricted due to the technically demanding nature of the MIDP especially with the straight rigid instruments used in conventional laparoscopy.…”
Section: Introductionmentioning
confidence: 99%
“… 1 - 3 Laparoscopic surgery confers many benefits such as smaller surgical scars, reduced blood loss, and faster recovery times. 4 - 6 Nonetheless, its widespread adoption remains restricted due to the technically demanding nature of the MIDP especially with the straight rigid instruments used in conventional laparoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…32 Subsequent reports predominantly still combined outcomes for isolated robotic-assisted approaches with other minimally invasive techniques. [33][34][35] Georgakis et al reported the first series of robotic resections in a cohort of patients from the United States (UPMC health care system, Pittsburgh) comparing 17 MIS resections including 14 robotic-assisted to 17 open resections with comparable operative and postoperative outcomes; however, a robotspecific comparison was not included in the analysis. 36 In 2019, Goel et al reported the first dedicated comparison of 27 robotic radical cholecystectomies to a control of open resections in patients treated at Tata Memorial Center in Mubai, India.…”
Section: Discussionmentioning
confidence: 99%